Profile of Meaningful Learning in Mathematics among Elementary School Students on Number and Operations Topics - Majid, Abdul; Latri, Latri; Bishri, Abdullah Azzam (International Journal of Education, Culture, and Society, 2026)
Although meaningful learning is essential in elementary mathematics, instruction on number and operations often remains procedurally oriented and offers limited opportunities for students to connect mathematical ideas with real-life contexts. This study aimed to analyze the profile of meaningful learning in mathematics among elementary school students on number and operations topics. The study employed a descriptive method with a qualitative approach supported by quantitative data and was conducted at SDN 50 Bonto Panno, Pangkep Regency, from October to November 2025. The participants were 25 fifth-grade students. Data were collected through contextual tests on number and operations, a meaningful learning questionnaire, classroom observations, and documentation of students’ work. Data analysis was conducted by categorizing students’ meaningful learning based on indicators of conceptual understanding, connections to real-life experiences, and the ability to explain and reflect on mathematical concepts. The findings showed that students’ meaningful learning in mathematics was generally at a moderate level. Although students demonstrated adequate procedural understanding of number operations, they experienced difficulties in linking mathematical concepts to contextual situations and in verbally explaining the meaning of the concepts learned. These findings indicate the need to strengthen contextual, reflective, and student-centered mathematics instruction to enhance meaningful learning in number and operations topics and contribute to improving foundational mathematics learning at the elementary school level.